2011
DOI: 10.1097/ncn.0b013e3181fcbddb
|View full text |Cite
|
Sign up to set email alerts
|

Using M-Learning on Nursing Courses to Improve Learning

Abstract: Modern handheld devices and wireless communications foster new kinds of communication and interaction that can define new approaches to teaching and learning. Mobile learning (m-learning) seeks to use them extensively, exactly in the same way in which e-learning uses personal computers and wired communication technologies. In this new mobile environment, new applications and educational models need to be created and tested to confirm (or reject) their validity and usefulness. In this article, we present a mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…JDOC and INMEDEA teach common procedures of the everyday work of doctors in different contexts and focus on doctor-patient interaction and medical diagnosis. Recent projects have tried to close the gap between computer-supported learning and reality by introducing learning support to mobile devices [20,21] ] . Improved collaboration induced by serious games in the nursing context was stressed some time ago [22]; in a more recent review of virtual 3-D medical learning environments the collaborative aspect was identified as a major strength associated with several game-oriented medical learning approaches based on virtual worlds [7].…”
Section: Introductionmentioning
confidence: 99%
“…JDOC and INMEDEA teach common procedures of the everyday work of doctors in different contexts and focus on doctor-patient interaction and medical diagnosis. Recent projects have tried to close the gap between computer-supported learning and reality by introducing learning support to mobile devices [20,21] ] . Improved collaboration induced by serious games in the nursing context was stressed some time ago [22]; in a more recent review of virtual 3-D medical learning environments the collaborative aspect was identified as a major strength associated with several game-oriented medical learning approaches based on virtual worlds [7].…”
Section: Introductionmentioning
confidence: 99%
“…Además se han publicado varias experiencias o casos de estudio en distintas universidades españolas. Por ejemplo, Ortega et al (2011) utiliza esta metodología en la enseñanza en enfermería; Contreras y Eguia (2009) muestra su experiencia educativa en la Universitat Politècnica de Catalunya donde los contenidos de aprendizaje se han distribuido mediante podcast; Furió, González-Gancedoa, Seguí y Costa (2013) presentan una experiencia basada en un juego utilizando iPhone y Tabletas; y Redondo et al (2014) muestra los usos del m-learning en el campo de la arquitectura y la edifi cación.…”
Section: El M-learning En Españaunclassified
“…Despit the ease of communication, using the technologymay be led to the transformation of identities and loss of human being in the virtual space. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
“…Like earlier digital instruments, mobile phones pave the way for new types of communication and interaction, which can also specify new paths to teaching. [ 1 2 ] In addition, generally speaking, participants have a positive view point concerning technology and investments in technology by universities and their workplace, despite the fact that their attitudes on applying such technologies for educational purposes remain obsolete. The majority of them determined laptop as the most effective ICT for education and learning, followed by learning management systems and smartphones.…”
Section: Introductionmentioning
confidence: 99%